Performance of the trading/services and finance sectors of the Kuala Lumpur stock exchange / Fauziah Ibrahim - Ibrahim, Fauziah (1997)
This study is a statistical analysis of a sample of companies of the Trading/Services and the Finance sectors of the KLSE.The research concentrates on 20 selected companies in these two sectors and gathering the data for five years to evaluate the performance of these based on the P/E ratio.The theory on the P/E ratio is 'a lower price earnings ratio will obtain a higher return'. Basically, the purpose of an investment is to obtain the highest return as much as possible whether in the appreciation of price or obtaining dividends. However, when we expect for a higher return, there will involve a higher risk. Since risk is vital in evaluating the return of stocks, three well known methods have been used. The Sharpe, Treynor and Jensen Index consider risks in evaluating the performance of stocks. The results mostly indicate a negative relationship between the P/E and return. Thus, the findings in this dissertation support the theory of the P/E ratio.